A new deep-water Tethya (Porifera, Tethyida, Tethyidae) from the Great Australian Bight and an updated Tethyida phylogeny - Sorokin, Shirley J.; Ekins, Merrick G.; Yang, Qi; Cárdenas, Paco (European Journal of Taxonomy, 2019)
A new species of Tethya Lamarck, 1815 is described from a depth of 1000 m on the continental slope of the Great Australian Bight (GAB), southern Australia. The GAB slope was explored as part of systematic benthic surveys to understand unexplored communities in the light of current oil and gas exploration activity in the area. Tethya irisae sp. nov. was present at 1000 m in six of eight longitudinal depth surveys. Three molecular markers were obtained: COI, 28S (D3–D5) and ITS1-5.8S-ITS2. COI and 28S phylogenetic analyses show that the new species fits clearly within the genus Tethya. This is the 28th species of Tethya reported from Australia; it is unusual in that it has a stalk. The presence of a stalk as a morphological character to split genera in this family is questioned. The description of this new species is an opportunity to revisit the molecular phylogeny of the Tethyida Morrow & Cárdenas, 2015 using comprehensive datasets of COI and 28S markers. As in previous analyses, four Tethya clades were retrieved; we discuss the possibility of using external colour to support some of these clades. Despite unclear phylogenetic relationships amongst Tethyidae Gray, 1848 from Australia, our results suggest that tethyid genera Tethytimea Laubenfels, 1936, Tectitethya Sarà, 1994, Laxotethya Sarà & Sarà, 2002, Stellitethya Sarà, 1994, and Xenospongia Gray, 1858 derive from species of Tethya. We show that asters have been secondarily lost at least twice in the Hemiasterellidae Lendenfeld, 1889: in Liosina Thiele, 1899 and a potential new genus from northern Australia. We formally propose the reallocation of Liosina from Dictyonellidae van Soest, Diaz & Pomponi, 1990 to Hemiasterellidae Lendenfeld, 1889.